Technical Assistance of the Soviet Specialists to China on Urban Planning in 1949-1959 - Li, Hao (International Planning History Society Proceedings, 2022)
A highlight of the urban planning activities in the early days of the People’s Republic of China was the massive number of professional Soviet specialists sent to technically assist China with urban planning. This was also a unique phenomenon in the international urban planning sector. More than forty Soviet specialists, who could be categorized into four series, were sent to China over a 10-year period to provide technical assistance, commencing from the arrival of the first series of Soviet municipal engineering specialists in August 1949 to the return of the last series of specialists in May 1959. By virtue of the technical assistance of the Soviet planners China managed to learn from Soviet planning theory in its entirety and developed urban reconstruction & expansion plans for a number of existing megacities as well as a number of important emerging industrial cities. Furthermore, thanks to the Soviet specialists, China was able to train and acquire a multitude of first-generation urban planners of its own who instilled into modern Chinese planning model a “cultural gene” which, originating primarily from the Soviet model, characterized socialist urban planning.